Thyroid Hormone Nuclear Receptor TRα1 and Canonical WNT Pathway Cross-Regulation in Normal Intestine and Cancer - Sirakov, Maria; Claret, Leo; Plateroti, Michelina (Frontiers in Endocrinology, 2021)
A pivotal role of thyroid hormones and their nuclear receptors in intestinal development and homeostasis have been described, whereas their involvement in intestinal carcinogenesis is still controversial. In this perspective article we briefly summarize the recent advances in this field and present new data regarding their functional interaction with one of the most important signalling pathway, such as WNT, regulating intestinal development and carcinogenesis. These complex interactions unveil new concepts and will surely be of importance for translational research.